Enhancement of Antioxidant Activity, Stability, and Structure of Heme-Peptides by L-Lysine - Yinghui Zhang; Wei Cui; Hui Zhou; Lifang Zou; Zhaoming Wang; Kezhou Cai; Baocai Xu (Foods)
Porcine blood is rich in protein and has always been the focus of research. Heme-peptides prepared from porcine hemoglobin are susceptible to oxidative degeneration during preparation and storage, thus affecting their function and stability. This study evaluated the enhancement effects of L-lysine (Lys) on recovery rate, antioxidant activity, stability, and structure. The results indicated that adding 1% Lys during enzymatic hydrolysis significantly increased the recovery rate of ferrous heme and peptide content by 93.88% and 15.30% (p < 0.05), respectively, and maximally enhanced antioxidant activity by 37.85% (p < 0.05). The contents of iron, ferrous ion, and ferrous heme in the heme-peptides were significantly increased by 97.52%, 121. 97%, and 74.45% (p < 0.05), respectively. Additionally, Lys improved the resistance to pH, temperature, metal ions, pepsin, and trypsin. Meanwhile, the effects of Lys resulted in heme-peptides with a smaller particle size, higher zeta potentials, and a smoother micromorphology. Fourier-transform infrared spectroscopy and fluorescence spectroscopy analysis showed that Lys enhanced the conformational stability of the heme-peptides. Molecular docking further suggested that hydrogen bonding was the main driver of the connections between Lys and the heme-peptides. This study provides theoretical guidance for the efficient utilization of heme-peptides in the food industry.